Capnodynamics – noninvasive cardiac output and mixed venous oxygen saturation monitoring in children - Karlsson, Jacob; Lönnqvist, Per-Arne (Frontiers in Pediatrics, 2023)
Hemodynamic monitoring in children is challenging for many reasons. Technical limitations in combination with insufficient validation against reference methods, makes reliable monitoring systems difficult to establish. Since recent studies have highlighted perioperative cardiovascular stability as an important factor for patient outcome in pediatrics, the need for accurate hemodynamic monitoring methods in children is obvious. The development of mathematical processing of fast response mainstream capnography signals, has allowed for the development of capnodynamic hemodynamic monitoring. By inducing small changes in ventilation in intubated and mechanically ventilated patients, fluctuations in alveolar carbon dioxide are created. The subsequent changes in carbon dioxide elimination can be used to calculate the blood flow participating in gas exchange, i.e., effective pulmonary blood flow which equals the non-shunted pulmonary blood flow. Cardiac output can then be estimated and continuously monitored in a breath-by-breath fashion without the need for additional equipment, training, or calibration. In addition, the method allows for mixed venous oxygen saturation (SvO2) monitoring, without pulmonary artery catheterization. The current review will discuss the capnodyamic method and its application and limitation as well as future potential development and functions in pediatric patients.